Assessing the extent to which performance management systems enhance performance in fulfilling objectives in an Integrated Development Plan : the case of Drakenstein Municipality, Western Cape - Prins, Whitney (Stellenbosch : Stellenbosch University, 2023)
Thesis (MPA)--Stellenbosch University, 2023.